'Tales of Wonder and Horror': Subject of Insanity in the Leeds Newspaper Press Miscellanies During the Late Georgian Era. (2nd July 2020) - Kryssova, Evgeniya
Abstract : This article explores the way in which leading Yorkshire newspapers, the Leeds Intelligencer and the Leeds Mercury, portrayed mental illness during the late Georgian era. In this period, newspapers were a central forum of public debate, yet a comprehensive analysis of the way they represented mental illness is lacking from the scholarship. Through the textual analysis of the newspaper miscellanies, this paper locates the subject of insanity within the middle-class Northern readership during the years of 1800 to 1840. The press content provides a fascinating glimpse of the opinions of the newly emerging psychiatric practitioners and the peculiarly middle-class fears and concerns about mental illness and its supposed increase.